2000
DOI: 10.1021/ac9910278
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Concentration Dependence and Response to Analyte Mixtures of Carbon Black/Insulating Organic Polymer Composite Vapor Detectors

Abstract: The responses relative to an air background of carbon black/polymer composite vapor detectors have been determined as a function of the concentration of a homologous series of alcohols (n-CnH2n+1OH, 1 < or = n < or = 8), a homologous series of alkanes (n-CnH2n+2, 5 < or = n < or = 10 and n = 12, 14), and a set of diverse solvent vapors. In all cases, the steady-state relative differential resistance responses, delta R/Rb, of the carbon black/polymer composite vapor detectors were well-described by a linear rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
168
0
4

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(177 citation statements)
references
References 33 publications
5
168
0
4
Order By: Relevance
“…In polymer calculations, the number of monomers in each chain is usually determined such that the total volume of the four chains is at least 6000 Å. 3 Alternatively, a degree of polymerization of 30 suffices to give values comparable to experiment. In such polymer samples, the minimum number of atoms is at least 1000.…”
Section: Ced Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In polymer calculations, the number of monomers in each chain is usually determined such that the total volume of the four chains is at least 6000 Å. 3 Alternatively, a degree of polymerization of 30 suffices to give values comparable to experiment. In such polymer samples, the minimum number of atoms is at least 1000.…”
Section: Ced Methodsmentioning
confidence: 99%
“…The pattern is unique and unambiguously identifies the compound. 3,23 The experimentally determined changes in relative resistivity, ⌬R/R, of seven polymer sensors upon exposure to 24 solvent vapors were correlated with the calculated Hansen solubility components. The permeability of a given odorant in a polymer is given by 24…”
Section: Electronic Nose Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reported that the steady-state DR/R b values for various carbon black-polymer composite chemiresistors are linearly dependent on analyte concentration over a range of analyte/detector combinations and analyte concentrations [31]. The noise measurements reported herein, in conjunction with the previously reported dependence of DR/ R b on the partial pressure of the analyte [30] and the analyte/ polymer sensitivity factors that can be deduced from such plots, allow estimation of the detection limits for various analyte/carbon black composite detector combinations.…”
Section: Detection Limits Of Chemiresistor-based Vapor Detectorsmentioning
confidence: 99%